Computational Analysis of Fluid Flow through a Sine-Curved Channel with High Reynolds Number. (21st October 2021) - Memon, Abid A.; Memon, M. Asif; Bhatti, Kaleemullah; Alotaibi, Hammad; Hamed, Y.S.; Shaikh, Gul M.; Khan, Ilyas
Abstract : In this paper, we attend to investigate the steady flow of a Newtonian fluid through a sine-curved channel working with the least-square technique of Galerkin's approach. We implement the whole simulation using Comsol Multiphysics 5.4. To study the fluid flow through this channel, we take the Reynolds numbers in the range from 1000 to 10, 000 and amplitude of the sine-curved channel in the range from 10 cm to 30 cm. We examine the flow rate and pressure at the outlet. It is observed that, at the outlet, maximum speed is increasing linearly along the Reynolds number and that the maximum pressure settled a negative relationship with the Reynolds number when increased. It is also determined that due to an increase in the hydraulic jumps, when increasing the amplitude of vibration of the channel, the velocity of flow got fluctuated at the above walls, which also results in a decline in the pressure from the inlet to exit of the channel. Moreover, the several correlations keeping amplitude as constant have been developed for the maximum flow velocity magnitude at the exit of the channel relating to the Reynolds number. These correlations will be definitely used for the future production and comparison for the fluid flow for the curvy channel.